(untitled) (Islamic Sciences Journal, 2023)
ABSTRACT This research discusses the efforts of Al-Khalil bin Ahmed Al-Farahidi and his opinions on the science of punctuation through the book The Decisiveness of punctuation in the Qur’an” by Abi Amr by al-Dani. The research discusses the development of punctuation, the stages it went through, its types, its causes, and the critical perspectives of scholars in its provisions. The research is concluded with the terms related to punctuation.